KAJIAN PENGGUNAAN PIPA PVC BENTUK BULAT DAN TALANG TRAPESIUM SEBAGAI INSTALASI IRIGASI DALAM USAHA HIDROPONIK TANAMAN SELADA (Lactuca sativa L.) - Ahmad Dalanggo; Leo H. Kalesaran; Daniel P. M. Ludong (COCOS, 2022)
Abstract This study aims to examine evapotranspiration in round pipes and trapezoidal gutters and their relationship to plant growth, assess the effect of microclimate on plant growth and production yields, calculate air efficiency, and analyze profit and loss using both types of pipes. This study was designed as an experimental study using 3 trapezoidal gutters and round pipes with a length of 4 m which were integrated into a water irrigation flow system using a pump, and each pipe used 20 planting holes. The results showed an average trapezoidal gutter evapotranspiration of 2334 , 67 ml of planting and in round pipes the average was 1955.50 ml of planting, the temperature in the pipe was around 29Â°C, the air temperature was around 30Â°C and the humidity was around 80%. plants in trapezoidal gutters had an average height of 17.49 cm, number of leaves 28, plant diameter 26.39 cm, leaf width 10.73 cm, leaf length 17.32 cm and total plant weight of 100.08 g, and plants in pipes spherical has an average height of 14.78 cm, number of leaves 24.58 strands, plant diameter 22.99 cm, leaf width 9.63 cm, leaf length 14.27 cm and total plant weight 65.52 g. liter of water in trapezoidal gutters produces 42.87 g of plant biomass, and every liter of water in the pipe produces 33.51 g of plant biomass, then the cultivation of circular lettuce plants in an area of 400 m2 using trapezoidal gutters gives sales results ranging from Rp. 116,937,216 every 1 year and lettuce plants on round pipes provide income of around Rp. 75,769,344 every 1 year.. Key words: Hydroponics, Hydroponics Irrigation, Hydrponics Lettuce